Is Tonsillolith a Protective Factor Against Covid-19 ? - Sevcihan Günen Yılmaz; Gamze Coşan Ata (European Annals of Dental Sciences)

(untitled)
Object: Tonsilloliths are the most common calcifications of the head and neck region and are also caused by inflammation of the pharyngeal lymphoid tissue. Changes that may occur in the lymphoid tissue due to tonsilloliths may affect the response to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). This radiological study aims to investigate the potential effect of tonsilloliths on Coronavirus disease 2019 (COVID-19).Material and Methods: This study, which has a cross-sectional retrospective design, was carried out by evaluating the digital panoramic radiographs taken before the pandemic period of the patient group (n=402) who had COVID -19, who applied to the Akdeniz University Faculty of Dentistry Oral, Dental and Maxillofacial radiology clinic, and the control group (n:400) who did not have COVID -19, in terms of the presence of tonsilloliths. All Statistical analyzes were performed with SPSS version 22.0 and P <0.05 was considered to indicate statistical significance. The Chi-square test and Student's t-test were performed.Results: The incidence of tonsillolith was significantly lower in the patient group (29.1%) than in the control group (45%) (p <0.01). Both groups were similar in terms of age, gender, and systemic disease status (p = 0.1, 0.08, and 0.08, respectively). Tonsilotiths were located both uni and bilaterally (p = 0.09), but unilateral ones were more common on the right side (p = 0.04).Conclusions: The results of this study showed that high-frequency tonsilloliths may have a protective effect against COVID -19.